EXTERNAL DEBT IS A THREAT TO NATIONAL SECURITY? - A D Antonova; E V Ponomarenko (RUDN Journal of Economics, 2016)
The article is devoted to one of the major problems of modern times - the issue of external public borrowing expansion and the ways public and total debt is managed in different countries.The article provides analytical overview of the current state of the world’s public finances and brief analysis of the global sovereign debt structure. Using the example of developed and emerging markets, the authors show us typical directions of the possible threats to the national economic security, and an acute need to develop effective national strategies for the external debt management.